PEMBARUAN PENDIDIKAN ISLAM AZYUMARDI AZRA: Melacak Latar Belakang Argumentasinya - Hastuti Baharuddin (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2013)
Abstrak: Pembaruan adalah proses atau cara membarui yang menghasilkan perubahan da-lam penyesuaian situasi dan kondisi. Pendidikan Islam adalah proses mempersi-apkan generasi muda (pembentukan individu) untuk menjalankan kehidupan (sebagai khalifah) dan untuk memenuhi tujuan hidup secara efektif dan efisien berdasarkan sumber-sumber Islam berupa al-Qura’n, sunnah, dan ijtihad. Pemba-ruan pendidikan Islam merupakan tuntutan kebutuhan dunia pendidikan Islam saat ini. Melihat ketertinggalan dan keterbelakangan umat Islam dewasa ini, maka inti dari pembaruan pendidikan Islam adalah berupaya meninggalkan pola pikir lama yang tidak sesuai dengan kemajuan zaman (future oriented) dan berupa meraih aspek-aspek yang menopang untuk menyesuaikan diri dengan kema-juan zaman. Pendidikan Islam yang sebenarnya adalah balanced between worldly life and hereafter (keseimbangan antara dunia dan akhirat), balanced between revealed knowledge and acquired knowledge (keseimbangan antara pengetahuan wahyu dan pengetahuan usaha manusia), balanced between iman-taqwa and science and technology (keseimbangan antara imtak dan iptek) sehingga menghasilkan kesejahteraan spiritual dan material.Abstract: Renewal is a process or a way of renewing the adjustment results in a change in circumstances. Islamic education is the process of preparing the younger genera-tion (generation people) to run life (as Caliph) and to meet life goals effectively and efficiently based on the Islamic sources, the Qur'an, the sunnah, and ijtihad. Renewal of Islamic education is a demand to the needs of Islamic education in this time. Seeing underdevelopment and backwardness of Muslims today is that the core of the reform of Islamic education is attempting to leave the old mindset that is not in accordance with the progress of time (future oriented) and strive for sustaining aspects to conform with the progress of time. Islamic education is actually is balanced between worldly life and hereafter, balanced between revea-led knowledge and acquired knowledge, balanced between iman-taqwa and science and technology so that resulting spiritual well-being and material well-being.